Old muscle in young body: an aphorism describing the Chronic Fatigue Syndrome - Tiziana Pietrangelo; Stefania Fulle; Francesco Coscia; Paola Virginia Gigliotti; Giorgio Fanò-Illic (PAGEPress Publications, 2018)
The chronic fatigue syndrome (CFS) otherwise known as myalgic encephalomyelitis (ME), is a debilitating syndrome whose identification is very complex due to lack of precise diagnostic criteria. This pathology begins with limitations in duration and intensity of exercise and rapid onset of pain during physical activity. Its etiology is unknown, and symptoms are not limited to the muscles. Epidemiology is rather difficult to delimit, even if it affects mainly young (20-40 years), female subjects. The results of muscular research show some peculiarities that can justify what has been observed in vivo. In particular, 1. presence of oxidative damage of lipid component of biological membranes and DNA not compensated by the increase of the scavenger activity; 2. Excitation-Contraction (E-C) alteration with modification of Ca2+ transport; 3. passage from slow to fast fiber phenotype; 4. inability to increase glucose uptake; 5. presence of mitochondrial dysfunction; and 6. genes expressed differentially (particularly those involved in energy production). The skeletal muscles of CFS / ME patients show a significant alteration of the oxidative balance due to mitochondrial alteration and of the fiber phenotype composition as shown in sarcopenic muscles of the elderly. Vice versa, the muscle catabolism does not appear to be involved in the onset of this syndrome. The data support the hypothesis that patients with CFS are subjected to some of the problems typical for muscle aging, which is probably related to disorders of muscle protein synthesis and biogenesis of mitochondria. Patients with CFS can benefit from an appropriate training program because no evidence suggests that physical exercise worsens symptoms. Type, intensity and duration of any physical activity that activates muscle contraction (including Electrical Stimulation) require further investigation even if it is known that non-exhaustive physical activity decreases painful symptomatology.